The impact of pre-existing aortic stenosis and mitral regurgitation on patients with acute myocardial infarction - Muzafarova, Tamilla; Motovska, Zuzana; Kala, Petr; Hlinomaz, Ota; Hromadka, Milan; Vichova, Teodora; Mrozek, Jan; Šramko, Marek; Hutyra, Martin; Petr, Robert; Tomasov, Pavol; Ionita, Oana; et al. (Scientific reports, 2025)
The prevalence of left-sided valvular heart disease (VHD) increases with age, but data on the impact of pre-existing VHD in patients with acute myocardial infarction (AMI) are limited. We aimed to define the clinical characteristics and outcomes of AMI patients with pre-existing left VHD. The analysis is based on data from three merged national registries. The dataset included 47,436 patients admitted with AMI over a 5year period at all Cath Labs nationwide. Pre-existing VHD was diagnosed in 1,445 patients (3.0%), moderate-to-severe mitral regurgitation (MR) in 510 patients (35.3%), and moderate-to-severe aortic stenosis (AS) in 869 patients (60.1%). Patients with VHD had worse baseline characteristics, pre-existing coronary artery disease, more complicated in-hospital course with higher Killip class, lower left ventricular ejection fraction, and more comorbidities. Angiographically more frequent left main stenosis, TIMI flow 3 before PCI, less frequent stent implantation. Patients with pre-existing VHD had significantly higher 7-day (10.1% vs. 4.5%, p < 0.001), 30-day (16.0% vs. 7.0%, p < 0.001) and 1-year mortality (28.7 vs. 12.7%, p < 0.001) compared to patients without. Conclusions. Patients with pre-existing VHD and AMI are characterized by complicated in-hospital course with higher Killip class, lower ejection fraction, angiographically less severe stenosis, TIMI flow 3 prior to PCI, and less frequent stent implantation. This is a high-risk group with higher short - and long-term mortality and earlier intervention should be considered.
Keywords: Aortic Valve Stenosis; Female; mitrální insuficience; aortální stenóza; ženské pohlaví; Registries; lidé; Aged, 80 and over; Risk Factors; Male; Aged; rizikové faktory; Myocardial Infarction; lidé středního věku; registrace; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Mitral Valve Insufficiency; infarkt myokardu; Humans